ナンキョク ショウワキチ デノ ケイリュウ キキュウ ヲ モチイタ カブ タイリュウケン エアロゾル カンソク ノ ホウコク - 原, 圭一郎; ハラ, ケイイチロウ; 長田, 和雄; オサダ, カズオ; 山内, 恭; ヤマノウチ, タカシ; Hara, Keiichiro; Osada, Kazuo; Yamanouchi, Takashi (2007)
P(論文) 第46次南極地域観測隊は,上空の大気エアロゾルの性状と数濃度の季節を捉えるため,昭和基地において2005年1月6日から12月11日かけて,27回の係留気球によるエアロゾル観測を実施した.この観測は,第VI期5カ年計画のプロジェクト研究観測で行われている「エアロゾル集中観測」の一環として実施された.ここでは,通年で係留気球観測を実施するための計画や準備,実際の観測状況,問題点について報告する. The 46th Japanese Antarctic Research Expedition (JARE-46) carried out twenty seven tethered-balloon-borne aerosol measurements at Syowa Station for better understanding of aerosol chemical and physical properties in the lower troposphere from 6th January 2005 until 11 December 2005. This report summarizes the plan, preparation, field activities and some troubles/problems in the tethered-balloon observations. departmental bulletin paper